The Macro Stress Test of Credit Risk on American Banks Based on the Panel Vector Autoregression Model (Comparison Between Large and Small Banks) - Chai, Mengchen (2018)
The purpose of this project is to stress test the credit risk of American Banks. The credit risk of different banking groups in the United States is compared through a scenario setting of macro factors. The main grouping is made up of both large and small banking groups. Firstly, the macroeconomic factors that can be used in a model simulation from the Dodd-Frank Act are selected. Then the PVAR model is used to determine the causal relationship between inflation and unemployment on credit risk. The final section is mainly comprised of stress tests on different banking groups. The selection criteria for the stress test scenario was based on Dodd-Frank guidance. The results of the stress tests show that different groups of banks have differing sensitivities to macroeconomic changes. The response of small banks to the unemployment rate is shown to be more pronounced under the stress tests. Overall, unemployment rate increases a bank's credit risk, but the influence of inflation varies.